The Ever Widening Scope of Fact Review in Federal Appellate Courts—Is the “Clearly Erroneous Rule” Being Avoided? - John F. Nangle (Washington University Law Quarterly, 1981)
The expansion that has occurred in the federal courts is of principal concern to this writer.
Keywords: Appeals (Law); Appellate courts; Law and fact; Federal Rules of Civil Procedure; United States